World Bank & heavenly bank in poverty & prosperity: The case of Tanzanian faith gospel - Hasu, Päivi (Review of African Political Economy, 2006)
This article discusses the articulation of religious rhetoric with neoliberal principles of the market economy in Tanzania, looking specifically at Pentecostal-charismatic Christianity. Religion is interpreted here as a reflection of and model for a lived reality. On the one hand, a lived reality generates and shapes religious beliefs and ideas. On the other, religious beliefs and ideas inform the ways that economic circumstances are perceived, interpreted and acted upon in specific social and historical contexts. This is a discussion of charismatic Christian perceptions and of the perceived spiritual and economic changes in Tanzania ahead of the general election of 2005. These Biblical allegories, as well as the gospel of prosperity, are brought together through an account of the activities of one particular charismatic ministry. The rhetoric and logic of prosperity through giving are discussed within the anthropological notion of gift exchange as well as with some born-again understandings of the significance of offerings to God as a means to prosperity and accumulation.
free